2009
DOI: 10.1007/s00228-009-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of driving impairing medicines: a European survey

Abstract: AimTo analyse the consumption of a number of medicines with a known potential for increasing the risk of road traffic accidents in the general population of Europe.MethodsQuestionnaires were distributed through the European Drug Utilization Research Group (EuroDURG) and Post-Innovation Learning through Life-events of drugs (PILLS) networks. A total of 30 countries (the current EU Member States, Iceland, Norway and Switzerland) were asked to supply data on the use of driving impairing medicines for the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
(13 reference statements)
2
20
0
4
Order By: Relevance
“…High consumption of antihistamines in Norway and Sweden found in our study is in line with a previous drug utilisation survey [ 28 ], which proposed a higher data quality as potential reason for this finding. In this regard, each Country should check for data quality before definitively deciding regulatory strategies (e.g., Lithuania should verify its very low consumption of antihistamines, which may be due to issues of reimbursement restrictions similar to the situation for proton pump inhibitors and statins versus Western European countries [ 29 ]).…”
Section: Discussionsupporting
confidence: 92%
“…High consumption of antihistamines in Norway and Sweden found in our study is in line with a previous drug utilisation survey [ 28 ], which proposed a higher data quality as potential reason for this finding. In this regard, each Country should check for data quality before definitively deciding regulatory strategies (e.g., Lithuania should verify its very low consumption of antihistamines, which may be due to issues of reimbursement restrictions similar to the situation for proton pump inhibitors and statins versus Western European countries [ 29 ]).…”
Section: Discussionsupporting
confidence: 92%
“…Similar trends have been seen in other countries. From 2000-2005, both prescription opioid and benzodiazepine consumption increased 1.5-10% (Ravera et al 2009), whereas methadone (Ravera et al 2009) and barbiturate use remained relatively stable in Europe (Nicholas et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the signal arose from the German SRS, although no recent drug utilization data are publicly available. A previous European cross-national comparison study on aggregated data (2000–2005 period) reported an unexpected low use of reimbursed antihistamines, which was interpreted in the light of legislation on over-the-counter products [ 29 ]. The latest European drug utilization analysis found that levocetirizine was largely used in France, where the drug represented 53 % of the total defined daily doses of antihistamines [ 12 ].…”
Section: Discussionmentioning
confidence: 99%